Modern weapons and military equipment for issue 2/2014 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The need for speed First for Europe Secret New UAS shows stealth, efficiency advances Sattelite imagery shows "supergun" in Chinese desert Iran launches new submarine class Pakistan inducts first "indigenous" UAV India finally commissions ex-Russian aircraft carrier China fields new 105 mm assault gun vehicle China reveals new details about CM-400AKG